Pemanfaatan Enzyme-Linked Immunosorbent Assay untuk Mengukur Titer Virus dalam Bawang Putih - Susamto Somowiyarjo; Endang Mugiastuti; Y. M. Sugi Maryudani (Jurnal Perlindungan Tanaman Indonesia, 2000)
Non-precoated Indirect ELISA had been developed by employing monoclonal antibodies against virus isolated from Sangga variety of garlic. The ELISA was used to measure the titer of virus in the plant. In comparation with biological assay using Chenopodium amaranticolor, ELISA was able to measure the virus titer faster and was more simpler. The highest titer of virus was obtained using the first leaf of garlic at age of 29-36 days after planting. Application of nitrogen at high dose and high temperature of garlic cultivation trends to increase the virus titer. The results of this experiment may be used to improve the method of sampling to detect virus in garlic tissues.